DISTRIBUSI PENDAPATAN KESEJAHTERAAN MENURUT KONSEP EKONOMI ISLAM - An’im Fattach (JPIM (Jurnal Penelitian Ilmu Manajemen), 2018)
Islamic Economics with the idea of giving the economy the principles of life in a relationship with each other. In it contains the direction and at the same time demand that his followers do your best and avoid action that is considered a sin. Islamic economics does not just contain about sets of rules but provides a guarantee for improved welfare. In this article, the authors intend to reveal the clarity of the distribution of income: welfare according to the concept of Islamic economics. Islam considers that economic prosperity is not solely economic problems of distribution of material, but also involves an element of non-material and other fields. Economic welfare can be run in conjunction with welfare in other fields. Islamic economic demands for the overall running of the teachings of Islam in all aspects of life. The consequence of this concept is the well-being should be viewed as a manifestation of God's command to his servant. So that the welfare of the continuing e orts of mankind to do good, both to God and to fellow human beings. Keywords: Distribution, Income, Welfare, Islamic Economic